Metabolic Effects of Ketogenic Diets - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The results of 24 metabolic profiles performed on 55 epileptic children receiving the classical ketogenic diet, the MCT diet, a modified MCT diet, and normal diets are reported from the University Department of Paediatrics, John Radcliffe Hospital, Oxford, England.